Digital marketing as a digital revolution in marketing communication - Chomiak-Orsa, Iwona; Liszczyk, Konrad (Digital marketing jako cyfrowa rewolucja komunikacji marketingowej, 2020)
Today’s market has been subordinated to the information which, to a large extent, reaches us in an uncontrolled way at any time. Thus the article presents the key factors resulting from the forms of communication which influenced the creation of digital marketing, i.e. the resultant soft features derived from interpersonal interactions and the technological aspects which are the channels of communication, thanks to which the transmission of information and its reception can take place through a mass recipient and sender. The aim of the article is to illustrate the relations between communication and marketing, from interpersonal communication through marketing and Internet communication. The research method used in the article was a critical analysis of literature and identification with the characteristics of technological solutions in the area of digital marketing available on the market
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 2 (56), s. 9-19
Keywords: marketing; marketing communication; internet communiaction; digital marketing; digital marketing channels; content marketing; komunikacja marketingowa; komunikacja internetowa; marketing cyfrowy; kanały marketingu cyfrowego; marketing treści